Incidence of myopia and biometric characteristics of premyopic eyes among Chinese children and adolescents - Lan Li; Hua Zhong; Jun Li; Cai-Rui Li; Chen-Wei Pan (BMC Ophthalmology, 2018)
Abstract Background To determine the one-year incidence and progression rates of myopia and its association with baseline ocular biometric parameters in school-based samples of children and adolescents in China. Methods Two thousand four hundred thirty two grade 1 and 2346 grade 7 students living in the southwest part of China participated in the baseline survey. After 1 year, 2310 (95.0%) grade 1 and 2191 (93.4%) grade 7 students attended the follow-up examination. Refractive error was measured after cycloplegia using the same autorefractor and by the same optometrists in the baseline and follow-up examination. Myopia was defined as spherical equivalent of less than − 0.50 diopter. Results The overall one-year incidence of myopia was 33.6% (95% confidence interval [CI]: 31.7–35.5) among grade 1 students and 54.0% (95% CI: 51.5–56.5) for grade 7 students. The one-year myopia progression rate was − 0.97 D (95% CI: -1.22 to − 0.71) in grade 1 students and − 1.02 D (95% CI: -1.07 to − 0.96) in grade 7 students. Per mm increase in baseline axial lengths increased the risk of myopia onset by 28% among grade 1 students and 22% among grade 7 students after 1 year. The incidence rates of myopia were found to be higher in grade 7 students with thinner premyopic lenses. Conclusions The incidence and progression rates of myopia were very high in Chinese children and adolescents in recent years. Premyopic eyes were characterized with longer axial lengths and thinner lenses. These data had considerable implications for formulating myopia prevention strategies in China.